Psychological outcomes and associated factors amongst healthcare workers during a single wave, deeper into the COVID-19 pandemic in China - Tang, Jianyong; Wu, You; Qi, Hongyan; Li, Dongjing; Shi, Jianfei; Wang, Wei; Niu, Mengmeng; Liu, Liang; Wang, Dong; Li, Xia (Frontiers in Psychiatry, 2022)
Background: To date, the novel coronavirus disease 2019 (COVID-19) pandemic has repeatedly broken out across many regions in China, and caused continuous physical and mental harm to health care workers. This study investigates the psychological burden and associated risk factors among Chinese healthcare workers (HCWs) during the repeated waves of COVID-19 pandemic. Methods: This cross-sectional web-based survey was conducted from January 16, 2022 to February 5, 2022. A total of 412 HCWs from Northwestern China were recruited in this study. The socio-demographic data and COVID-19 related survey variables were collected using online self-rating questionnaires. The Chinese versions of well-validated instruments to assess the mental health status, including 12-item General Health Questionnaire for psychiatric morbidity, Generalized Anxiety Disorder Scale-7 for anxiety, Patient Health Questionnaire-9 for depression, and Insomnia Severity Index-7 for insomnia. Multivariate logistic regression analysis was performed to identify risk factors associated with the psychological outcomes. Results: Among the 388 participants who were included in the final study (94.17% response rate), the prevalence of anxiety, depression, and insomnia symptoms were 25.3% (95% CI: 20.9-29.6%), 40.7% (95% CI: 35.8-45.6%), and 30.9% (95% CI: 26.3-35.5%), respectively. Multivariate logistic regression analysis revealed that being a woman and had a perceived need for psychological support were the risk factors for all psychological outcomes. Poor disease cognition and perceived susceptibility were risk factors for anxiety, unvaccinated against COVID-19 and poor disease cognition were risk factors for depression, and unvaccinated against COVID-19 was an independent risk factor for insomnia. Conclusions: Our study has identified a relatively lower prevalence rate of psychological disorders among Chinese HCWs during the repeated waves of COVID-19 pandemic. Female HCWs, and HCWs who had a perceived need for psychological support, had a poor disease cognition, were perceived as susceptible to COVID-19 and had not been vaccinated against COVID-19 need more attention.